2022
DOI: 10.1080/21505594.2022.2035066
|View full text |Cite
|
Sign up to set email alerts
|

Sodium houttuyfonate enhances the mono-therapy of fluconazole on oropharyngeal candidiasis (OPC) through HIF-1α/IL-17 axis by inhibiting cAMP mediated filamentation in Candida albicans-Candida glabrata dual biofilms

Abstract: Candida albicans and Candida glabrata are two common opportunistic fungi that can be co-isolated in oropharyngeal candidiasis (OPC). Hypha is a hallmark of the biofilm formation of C. albicans , indispensable for the attachment of C. glabrata, which is seldom in mycelial morphology. Increasing evidence reveals a hypoxic microenvironment in interior fungal biofilms, reminding of a fact that inflammation is usually accompanied by oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…Accumulating evidences suggest that cAMP plays an essential role in regulating filamentation in C. albicans . Increased intracellular cAMP promotes hyphal growth [ 27 ]. Thus, we examined the effect of MPD on the intracellular cAMP concentrations of C. albicans .…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating evidences suggest that cAMP plays an essential role in regulating filamentation in C. albicans . Increased intracellular cAMP promotes hyphal growth [ 27 ]. Thus, we examined the effect of MPD on the intracellular cAMP concentrations of C. albicans .…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers have reported biofilms in almost all natural and industrial ecosystems, especially in infectious diseases [ [15] , [16] , [17] , [18] , [19] , [20] ]. Bacterial biofilms can lead to chronic infection.…”
Section: Discussionmentioning
confidence: 99%
“…71,72 After SH management, the gut microbiota imbalance could be largely recovered. Although SH is generally considered to be an antibacterial drug, it has been found that the in vitro antibacterial MIC of SH was relatively high (>128 μg mL −1 ) in comparison with its antifungal MIC (<64 μg mL −1 ), [73][74][75][76] implying a more effective activity of SH against fungi than against bacteria. Although bacteria are predominant in the gut, their abundance and compositions can be greatly impacted by excessive colonization of C. albicans.…”
Section: Food and Functionmentioning
confidence: 99%